Analisis Perawatan Mesin Injection Moulding dngan Metode RC dan FMEA di PT “X” - Etik Puspitasari; Vinan Viyus; Nurchajat; Talifatim Machfuroh (G-Tech: Jurnal Teknologi Terapan, 2024)
PT. "X" is an injection molding company. Machine maintenance and repair are very influential on a stable production rate. The purpose of the research is to find the root cause of the problem of plastic molding machine damage and find the right accurate solution, and also which parts are prioritized for repair using the RCA and FMEA methods. The Results of the RCA method analysis for injection molding machine maintenance. Four priority parts experience mechanical part wear. The root cause of the problem is the first part pin and bushing experience wear due to lack of lubrication due to lack of visual checking maintenance. The second part of the platen surface has wear due to uneven molding, and also by checking the mold if the mold material is harder, the platen will lose or the platen surface has dented. The third part of the Mold Adjust Pitch Tie Bar and Pitch Gear experiences wear and tear due to the nut thread wear due to the high press of the thread that becomes a fulcrum. The fourth part of the Adjustable Nut, namely the Locking Nut, does not function because the locking nut is not balanced and not parallel, causing flashing. For the analysis of the FMEA method of injection molding machine maintenance based on the RPN value, the order of priority parts for preventive maintenance is Pin and bushing, Platen surface, Mold Adjust Pitch Tie Bar and Pitch Gear, and Adjustable Nut.